The Performance of Bamboo Fiber as Fine Aggregate Replacement in Concrete - Mohd Noh, Hamidun; Mohamad, Nur Atiqah; Idris, Nur'ain; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam (International Journal of Integrated Engineering, 2021)
The rapid growth of construction industry has caused a huge demand on natural aggregate as the production of concrete requires massive use of natural stone materials. Due to the increase of demand of this material, it has affected to the shortage of natural aggregate and increased the cost of construction material. On the other hand, bamboo is one of the materials which have a big population and potential to be used in construction due to its durability, flexibility and strength performance. So, bamboo fiber was used as aggregate replacement material to reduce the cost of construction material and pollution as well as to improve the quality of the concrete. The research objectives in this study are to determine the optimum percentage of bamboo fiber as aggregate replacement in concrete and to compare the compressive strength of the bamboo fiber concrete with standard concrete. There were 4 cube specimens casted for each proportion of 0%, 5%, 12.5%, 10%, 12.5%, 15% and 17.5% of bamboo fiber as aggregate replacement in concrete. Then, the compressive strength test was conducted to find the optimum bamboo fiber contents with the maximum workability and strength of the concrete. The findings showed that the replacement of 5% of bamboo fiber achieved the highest strength with 27.77 N/mm2 and the strength decrement difference is only about 2.38% with standard concrete. Based from the result, the 5% bamboo fiber concrete can be suggested as the optimum percentage of bamboo fiber as aggregate replacement in concrete. This study is not only aim in reducing the cost of construction material but it also can be one of the effectives ways to reduce environmental impact by using natural fibers as aggregates replacement.